PEMERTAHANAN BAHASA HELONG MELALUI PENERJEMAHAN CERITA RAKYAT BERBASIS IDEOLOGI PEMERASINGAN - Niron, Yakobus M Langkelang; Kami, Patrisius; Usfal, Nofriana (Jurnal Lazuardi, 2024)
The Helong language is currently experiencing degradation and is even threatened with extinction. The decrease in speakers, the existence of alternative language choices, and the increase in tourism are the causes of the problem of language resistance towards the Helong language. This research aims to bring up a vocabulary of cultural elements in translation which can be a solution in efforts to maintain the Helong language through folklore as a medium for transmitting the language. The translation process uses the SL-Emphasis Strategy (Nemark's V-Diagram Model) and the Newmark cultural content translation procedure as a form of translation based on foreignization ideology. A qualitative approach using the content analysis method was used to explore various in-depth information related to folklore speech, the meaning of cultural vocabulary, and the translation of the Helong language through traditional figures and various cultural literature as supporting input for the research. The results of this research lead to the ideology of alienation in the translation of five folk tales of the Helong community which contain elements of ecological culture, material culture, social culture, social organization, kial and customs which give rise to 74 vocabulary elements of the source language culture (Helong Language) in 92 sentences of the target language (Indonesian).